Nutritional Profile and Silage Quality of Avocado Seed Meal as Herbal Feed Additive Enriched with Molasses - Sadarman; Nurfitriani, Rizki Amalia; Harahap, Rakhmad Perkasa; Saleh, Eniza; Anugrah; Alfian, Aldi; Juliantoni, Jepri; Alridho, Dwi Putra Agung; Febrina, Dewi; Sastrawan, Sandri; Adegbeye, Moyosore Joseph; Khairi, Fitrah (Jurnal Nutrisi Ternak Tropis, 2025)
Avocado seed meal, a part of the avocado plant that is rich in antioxidants and various other nutrients and non-nutrient substances, has great potential to be utilized as an herbal additive in animal feed. This study aims to determine the effect of molasses addition on the nutrient profile and quality of avocado seed meal silage. The control treatment (P1) used plain avocado seed flour, while the experimental treatments (P2, P3, P4, and P5) incorporated increasing molasses concentrations of 1%, 1.50%, 2%, and 2.50% of dry matter, respectively. All treatments were silaged for 30 days at room temperature. Key parameters measured were nutrient content, temperature, pH, fungal growth, physical and fresh silage quality, dry matter loss, and Fleigh value. The data obtained were analyzed based on analysis of variance, differences in parameter values between treatments were further tested with DMRT at the 5% significance level. Results indicated that molasses significantly enhanced the silage's nutrient content and improved its physical and fresh quality by optimizing temperature, reducing dry matter loss, and increasing Fleigh value (P<0.05). The conclusion of this study suggests that adding 2.50% molasses can produce the highest-quality avocado seed meal silage as an optimal herbal feed for livestock.